Developing Gen-21cs on smartphone to cultivate the 21st-century skills on biology teacher candidates - Maryuningsih, Yuyun; Hidayat, Topik; Riandi, R.; Rustaman, Nuryani (University of Muhammadiyah Malang, 2019)
The accessibility of learning media is one of the determining factors of student skills in dealing with the 21st-century demands. This study aimed at developing the online-discussion-forum-based Gen-21cs application. This Research and Development (R&D) used the Ellis and Levy Model which comprised of six phases, namely, 1) identifying the problem by determining learning indicators and supporting literature, 2) determining the purpose of development, 3) making the design and development of tools 4 ) approve device testing, 5) try device test results and 6) communicate device test results. The data gained were analyzed using descriptive qualitative. The development results showed that the Gen-21cs application can be used in learning process and facilitated students to conduct online discussion. Furthermore, the validation results indicated that the media was feasible to use with ?very good? category.